2016
DOI: 10.1038/srep26718
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic metal growth on phospholipid nanodiscs via lipid bilayer expansion

Abstract: Self-assembling biomolecules provide attractive templates for the preparation of metallic nanostructures. However, the intuitive transfer of the “outer shape” of the assembled macromolecules to the final metallic particle depends on the intermolecular forces among the biomolecules which compete with interactions between template molecules and the metal during metallization. The shape of the bio-template may thus be more dynamic than generally assumed. Here, we have studied the metallization of phospholipid nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…480 Deposition of colloidal Au particles resulted in rapid lateral growth of Nanodiscs during the first few minutes. At the same time appearance of optical absorption in the near-UV region below 440 nm was observed.…”
Section: Nanodisc Applications In Biotechnology and Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…480 Deposition of colloidal Au particles resulted in rapid lateral growth of Nanodiscs during the first few minutes. At the same time appearance of optical absorption in the near-UV region below 440 nm was observed.…”
Section: Nanodisc Applications In Biotechnology and Medicinementioning
confidence: 99%
“…Negatively charged nanodiscs assembled using MSP1D1 and DMPG lipids were used as templates for making composite nanoparticles by electrostatic absorption of positively charged 1.4 nm amine coated gold nanoparticles. 494 Deposition of colloidal Au particles resulted in rapid lateral growth of nanodiscs during the first few minutes. At the same time, appearance of optical absorption in the near-UV region below 440 nm was observed.…”
Section: Nanodiscs and Nanomaterials Engineeringmentioning
confidence: 99%
“…Recent studies demonstrated that NPprotein corona formation could interact with many immune system components to either stimulate or suppress the immune response and cytotoxic effects (Hu et al, 2011a;Ruge et al, 2011;Lee et al, 2015;Lu et al, 2018). In addition, various coating materials like polyethylene glycol (PEG), poly (lactic-co-glycolic acid) (PLGA), polylactic acid (PLA), lipids, and others have been used to modify the metalbased NP surface, which considerably changes the physicochemical properties of NPs (Tefft et al, 2015;Oertel et al, 2016;Guerrero et al, 2019;Jiao et al, 2020;Murphy et al, 2021). Surface modifications of NPs not only affect their pharmacokinetics and change their biodistribution, clearance, and elimination, which are closely related to their toxicity in the body (Arami et al, 2015;Das et al, 2017;Yu et al, 2018a).…”
Section: Physicochemical Properties Of Metalbased Nanoparticles That ...mentioning
confidence: 99%
“…Self-assembly of hierarchically ordered structures is a fascinating subject, in which small entities into larger two- or three-dimensional (3D) structures exhibiting new features that cannot be achieved by the isolated building blocks. , Nature uses a highly ordered self-assembled structure to construct the functional hybrid materials from inorganic and organic building blocks. , The artificial synthesis of hierarchically self-assembled nanoscale building blocks such as nanoclusters, nanowires, nanobelts, and nanotubes is the versatile technique available for the fabrication of functional electronic and photonic nanodevices. , Fractal structures are extremely familiar in nature with different scales of lengths from self-assembled molecules, to the shapes of coastlines, to the distribution of galaxies, and even to the 3D shapes of clouds . They are never-ending patterns and are attained by repeating a simple process over and over in an ongoing reaction loop driven by recursion.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The artificial synthesis of hierarchically self-assembled nanoscale building blocks such as nanoclusters, nanowires, nanobelts, and nanotubes is the versatile technique available for the fabrication of functional electronic and photonic nanodevices. 5,6 Fractal structures are extremely familiar in nature with different scales of lengths from self-assembled molecules, to the shapes of coastlines, to the distribution of galaxies, and even to the 3D shapes of clouds. 7 They are never-ending patterns and are attained by repeating a simple process over and over in an ongoing reaction loop driven by recursion.…”
Section: ■ Introductionmentioning
confidence: 99%